2021
DOI: 10.1101/2021.10.29.466420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analysis of behavioral dynamics in the protochordateCiona intestinalis

Abstract: Locomotion is broadly conserved in the animal kingdom, yet our understanding of how complex locomotor behaviors are generated and have evolved is relatively limited by the lack of an accurate description of their structural organization. Here we take a neuroethological approach to break down the motor behavioral repertoire of one of our nearest invertebrate relative, the protochordate Ciona intestinalis, into basic building blocks. Using machine vision, we track thousands of swimming larvae to obtain a feature… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 104 publications
(165 reference statements)
0
3
0
Order By: Relevance
“…For instance, mechanical stimulation of the adhesive/sensory papillae, the three sensory organs (two dorsal and one ventral) located in the anterior larval region (Figures 1E, 2A-B) is sufficient and necessary to trigger metamorphosis in Ciona (Wakai et al, 2021;Sakamoto et al, 2022). While mechanosensitive modulation of swimming has yet to be definitively shown in ascidian larvae, startle-like behaviors have been described in Ciona (Athira et al, 2022). Here we discuss what is known about the development and function of the candidate primary mechanosensory cell types that have been identified in these larvae.…”
Section: Putative Mechanosensory Cells Of the Ascidian Larvamentioning
confidence: 99%
“…For instance, mechanical stimulation of the adhesive/sensory papillae, the three sensory organs (two dorsal and one ventral) located in the anterior larval region (Figures 1E, 2A-B) is sufficient and necessary to trigger metamorphosis in Ciona (Wakai et al, 2021;Sakamoto et al, 2022). While mechanosensitive modulation of swimming has yet to be definitively shown in ascidian larvae, startle-like behaviors have been described in Ciona (Athira et al, 2022). Here we discuss what is known about the development and function of the candidate primary mechanosensory cell types that have been identified in these larvae.…”
Section: Putative Mechanosensory Cells Of the Ascidian Larvamentioning
confidence: 99%
“…Recent research revealed that ascidian larvae exhibit multiple types of swimming, and their tail curvature varies depending on the stimulus. (Athira et al, 2022;McHenry, 2001;Nishino et al, 2011). Further analysis and fine tuning of DeepLabCut training data might be required to analyze the correlation between Ca 2+ oscillations and these various types of swimming in detail.…”
Section: Phases V and Vimentioning
confidence: 99%
“…intestinalis a marine invertebrate chordate that belongs to the sister group of vertebrates 12,13 and has a biphasic cycle which entails a tadpole-shaped, freely swimming larva which undergoes metamorphosis to generate the filter feeding adult [14][15][16][17][18] . C. intestinalis larvae possess a small optically accessible nervous system suitable for functional imaging 19 , with a fully mapped synaptic connectome 20,21 , which generates a rich behavioral repertoire 22 making them an ideal system for studying the sensory mechanisms underlying attachment, settlement, and metamorphosis of marine larvae. Previous studies have provided a detailed description of the morphogenetic steps that take place during settlement and metamorphosis over the course of a few hours 14,17,18 .…”
Section: Introductionmentioning
confidence: 99%